2008
DOI: 10.1007/s12210-008-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of proline in plant stress tolerance and development

Abstract: The recent progresses in the research on proline will be described, focusing on plants and covering proline metabolism and signal transduction as well as the role of this imino acid in stress response. Furthermore, the recently described developmental role of proline in flowering and reproduction will be illustrated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(144 citation statements)
references
References 115 publications
(154 reference statements)
2
135
0
7
Order By: Relevance
“…Table 6. The effect of NaCl, proline and their interaction on the height (cm) (A) and leaf number (B) of Citrus sinensis (L.) Osbeck plantlet (Abbas et al, 2012 Physiological role of proline Proline at optimum level has several roles such as osmoprotectant, turgor generation, storage of carbon and nitrogen, maintenance of the structure of proteins, maintenance of cytosolic pH, balance of redox status,acting as a part of stress signal, an inhibitor of lipid membrane peroxidation and antioxidant as effective quencher of ROS formed under stress conditions in plants (Maggio et al, 2002;Ashraf and Foolad, 2007;Trovato et al, 2008;Hayat et al, 2012).…”
Section: Effective Doses Of Prolinementioning
confidence: 99%
“…Table 6. The effect of NaCl, proline and their interaction on the height (cm) (A) and leaf number (B) of Citrus sinensis (L.) Osbeck plantlet (Abbas et al, 2012 Physiological role of proline Proline at optimum level has several roles such as osmoprotectant, turgor generation, storage of carbon and nitrogen, maintenance of the structure of proteins, maintenance of cytosolic pH, balance of redox status,acting as a part of stress signal, an inhibitor of lipid membrane peroxidation and antioxidant as effective quencher of ROS formed under stress conditions in plants (Maggio et al, 2002;Ashraf and Foolad, 2007;Trovato et al, 2008;Hayat et al, 2012).…”
Section: Effective Doses Of Prolinementioning
confidence: 99%
“…Furthermore, during flower, embryo and other developmental processes it may support the energetic needs of rapidly dividing or elongating cells. 3,19 Proline was found to be the most abundant amino acid in mature and germinated Arabidopsis pollen, accounting for 60-65% of the free amino acid pool. 20 Water stress at maize tassel initiation showed a greater influence on proline, ABA levels and yield than that at anthesis.…”
Section: Resultsmentioning
confidence: 99%
“…However the expansion of oxidative stress research has given many new insights into the role of proline in plants. Today it is clear that proline is a multifunctional amino acid [1][2][3][4] with many metabolism pathways being revealed. [5][6][7] The proline concentrations of cells, tissues and plant organs are regulated by the interplay of biosynthesis, degradation and intra-as well as intercellular transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, those compatible solutes are often designated as osmoprotectors. Proline and trehalose are some of the main compatible solutes largely studied in the evaluation of plants to detect tolerance to drought, and often used as plant breeding tool to segregate sensible and tolerant genotypes (Trovato et al, 2008;Anami et al, 2009). Although trehalose has been considered as osmoprotector, lately some authors have reported that it should not be regarded only as a protective sugar, and that further investigation is required to elucidate its exact role in the stress tolerance in plants (Paul et al, 2008;Fernandez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although trehalose has been considered as osmoprotector, lately some authors have reported that it should not be regarded only as a protective sugar, and that further investigation is required to elucidate its exact role in the stress tolerance in plants (Paul et al, 2008;Fernandez et al, 2010). It is also advocated that trehalose and proline are used as energy sources, and that proline may be metabolized as nitrogen source readily available for plant re-establishment just after the period of water limitation (Kavi Kishor et al, 2005;Trovato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%